The influence of cervical traction, compression, and spurling test on cervical intervertebral foramen size - Takasaki, H.; Hall, Toby; Jull, G.; Kaneko, S.; Iizawa, T.; Ikemoto, Y. (Lippincott, Williams and Wilkins, 2009)
Study Design. A comparative measurement design investigating the C4-Th1 intervertebral foramen under simulated clinical tests for cervical radiculopathy using magnetic resonance imaging. Objective. The purpose of this study was to evaluate functional changes in the cervical intervertebral foramen during the axial compression test (ACT), axial distraction test (DT), and Spurling test (SST). Summary of Background Data. Although alterations of the cross-sectional area of the cervical intervertebral foramen during flexion/extension and rotation have been reported, there are no studies that have measured functional changes in foramen cross-sectional area (FCSA) or shape during the simulation of clinical tests for cervical radiculopathy. Methods. 23 participants (12 men, age: 24.52 years) without history of significant spinal disorders were studied. The 3-dimensional sequence of the magnetic resonance imaging of the foramen was performed with a 0.2-T horizontally open unit. Measurements were taken of FCSA and foramen shape (ratio of foramen height to FCSA). These measurements were conducted under 4 different conditions; control-resting in supine, DT-neck in neutral with a 12 kg distraction force, ACT-neck in neutral with a 7 kg axial compression force, SST-the cervical spine was extended (12.79°), rotated (63.36°), and laterally flexed (28.49°), in a standardized manner. Results. At all levels except for C7-Th1, the FCSA significantly increased (P < 0.05) during the DT to around 120% of control. In contrast, FCSA significantly decreased to approximately 70% of control (P < 0.05) at all levels during the SST. In addition, there were significant differences (P > 0.05) in foramen shape between the ACT and SST condition, but only at the C4-C5 and C5-C6 levels. Conclusion. During 3 clinical tests for cervical radiculopathy functional, relevant, and changes in the cervical intervertebral foramen were evident particularly in the middle cervical spine. © 2009, Lippincott Williams & Wilkins.